Identification of SDG gene family members and exploration of flowering related genes in different cultivars of chrysanthemums and their wild ancestors - Ting Han; Muhammad Ayoub Khan; Yiming Wang; Wenchao Tan; Chenran Li; Penghui Ai; Wenqian Zhao; Zhongai Li; Zicheng Wang (BMC Plant Biology, 2024)
Abstract The SET domain genes (SDGs) are significant contributors to various aspects of plant growth and development, mainly includes flowering, pollen development, root growth, regulation of the biological clock and branching patterns. To clarify the biological functions of the chrysanthemum SDG family, the SDG family members of four chrysanthemum cultivars and three related wild species were identified; their physical and chemical properties, protein domains and conserved motifs were predicted and analyzed. The results showed that 59, 67, 67, 102, 106, 114, and 123 SDGs were identified from Chrysanthemum nankingense, Chrysanthemum lavandulifolium, Chrysanthemum seticuspe, Chrysanthemum × morifolium cv. ‘Hechengxinghuo’, ‘Zhongshanzigui’, ‘Quanxiangshuichang’ and ‘Jinbeidahong’, respectively. The SDGs were divided into 5–7 subfamilies by cluster analysis; different conserved motifs were observed in particular families. The SDGs of C. lavandulifolium and C. seticuspe were distributed unevenly on 9 chromosomes. SDG promoters of different species include growth and development, photo-response, stress response and hormone responsive elements, among them, the cis-acting elements related to MeJA response had the largest proportion. The expression of chrysanthemum SDG genes was observed for most variable selected genes which has close association with important Arabidopsis thaliana genes related to flowering regulation. The qPCR results showed that the expression trend of SDG genes varied in different tissues at different growth stages with high expression in the flowering period. The ClSDG29 showed higher expression in the flower and bud tissues, which indicate that ClSDG29 might be associated with flowering regulation in chrysanthemum. In summary, the results of this study can provide a basis for subsequent research on chrysanthemum flowering time regulation.